Farmers benefit from drought insurance in Uganda - Gachagua, Marygoretti (Technical Centre for Agricultural and Rural Cooperation, 2018)
An information service programme in Uganda is addressing reduced farm productivity in the country - caused mainly by drought - and enabling farmers to better plan their planting season by enhancing their access to weather information and recommended agronomic practices. The programme is expected to increase the income of farm households and contribute to curbing food insecurity in the region.